Endoplasmic reticulum stress in cardiomyopathies: from the unfolded protein response to therapeutic opportunities - Qiu, Yueqing; Chen, Zhenyi; He, Pingge; Wang, Zhentao (Frontiers in Cardiovascular Medicine, 2025)
The endoplasmic reticulum (ER), a central organelle responsible for maintaining protein homeostasis, calcium balance, and lipid metabolism, is essential for cardiovascular integrity. Functional disruption—referred to as endoplasmic reticulum stress (ERS)—has been recognized as a major pathogenic driver across diverse cardiovascular disorders. Under pathological conditions such as hypoxia, nutrient deprivation, or infection, sustained ERS activates the unfolded protein response (UPR). While initially adaptive, prolonged or excessive ERS initiates apoptotic cascades, severely impairing cardiomyocyte metabolism, structure, and survival. This review examines the pivotal contribution of dysregulated ERS to the pathogenesis of various cardiomyopathy subtypes, including dilated, diabetic, hypertrophic, and arrhythmogenic right ventricular forms. We outline how ERS fosters maladaptive cardiac remodeling by promoting cardiomyocyte apoptosis and exacerbating oxidative stress, ultimately leading to heart failure. Special attention is given to the complex crosstalk between ERS-related signaling pathways (e.g., PERK, IRE1α, ATF6) and disease progression, with detailed analysis of key regulatory molecules, pathogenic genetic variants, and epigenetic alterations. Integrating recent advances, we highlight the therapeutic potential of targeting ERS pathways as a novel approach to cardiomyopathy treatment, offering a conceptual framework for future translational research and precision medicine strategies.